2019
DOI: 10.1037/men0000187
|View full text |Cite
|
Sign up to set email alerts
|

Stress in strong convictions: Precarious manhood beliefs moderate cortisol reactivity to masculinity threats.

Abstract: In this study, we use an experimental framework to fill three existing gaps in the masculinities and health literatures. First, we examine the impact of masculinity threats on cortisol reactivity to understand how hegemonic masculinity gets “under the skin” to affect men’s health. Second, we test two variations of a masculinity threat, which represents an important methodological advance to understand which type of threat is most stressful. Third, we examine whether precarious manhood beliefs (agreement with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…Although precarious manhood beliefs and their correlates have been measured quantitatively in several different cultures (e.g., Himmelstein et al, 2019;Valved et al, 2020), this study represents the first systematic, global examination of these beliefs using a standardized scale.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although precarious manhood beliefs and their correlates have been measured quantitatively in several different cultures (e.g., Himmelstein et al, 2019;Valved et al, 2020), this study represents the first systematic, global examination of these beliefs using a standardized scale.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, these findings extend the precarious manhood framework in novel ways. Although precarious manhood beliefs and their correlates have been measured both qualitatively and quantitatively in several different cultures (e.g., Himmelstein et al, 2019; Valved et al, forthcoming), this study represents the first systematic, global examination of these beliefs using a standardized scale. The findings reveal, first, that notions of precarious of manhood are universally understood, but endorsed to differing degrees across cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While biomarkers are still, at least technically, indirect measures of stress and physiological functioning, one of the primary advantages of such measures is that they are objective and minimize measurement error (Hellhammer et al, 2009). In addition, previous studies have also reported significant differences between objective (i.e., biomarkers) and subjective (i.e., self-reported) measures of stress, wherein both sets of measures are correlated with the measures of interest in opposite directions (Himmelstein et al, 2019). Therefore, alternative measurement strategies, focused on objective biomarkers, may offer greater precision and in turn, better identify associations of interest.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, (presumably cis) women who are more aware of sexism and feel less personal control report more distress from sexist events (Landry & Merucrio, 2009), and in experimental work, women who indicate that “being a woman” is important to their identity have stronger cardiovascular stress responses to a sexist social threat test (Eliezer et al, 2010). Masculinity beliefs may also influence stress response in women (Juster & Lupien, 2012) and cortisol reactivity in men (Himmelstein et al, 2019).…”
Section: Stress Biology and The Binarymentioning
confidence: 99%